2022
DOI: 10.3390/biotech11020018
|View full text |Cite
|
Sign up to set email alerts
|

Modern Aspects of Burn Injury Immunopathogenesis and Prognostic Immunobiochemical Markers (Mini-Review)

Abstract: Burn injuries are among the most common peacetime injuries, with mortality ranging from 2.3% to 3.6%. At the same time, 85–90% of patients with burns are people of working age and children. Burn injury leads to metabolic disorders and systemic inflammatory response, inefficient energy consumption, and other physiological changes that can lead to dysfunction of organs and systems. The most formidable complication of burn injuries is sepsis mediated by multiple organ failure, the most common cause of poor progno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…Secondly, no patient clinical outcome prediction exists. Although it is evident that the immune dysfunction induced by burn injury correlates with short- and long-term patient outcomes, there is no practical model with a predictive value that accurately reflects the underlying degree of immune insult and significantly correlates with the degree of compromise [ 17 ]. In addition, although multi-center bio-informatic studies have described the genomic storm after injury and initial attempts have been made [ 4 , 30 , 31 ], a profile of immune gene expression from burn patients that can be transformed into an “immune suppression index” has not been translated to the clinic, nor have these genomic markers been used to inform clinical care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Secondly, no patient clinical outcome prediction exists. Although it is evident that the immune dysfunction induced by burn injury correlates with short- and long-term patient outcomes, there is no practical model with a predictive value that accurately reflects the underlying degree of immune insult and significantly correlates with the degree of compromise [ 17 ]. In addition, although multi-center bio-informatic studies have described the genomic storm after injury and initial attempts have been made [ 4 , 30 , 31 ], a profile of immune gene expression from burn patients that can be transformed into an “immune suppression index” has not been translated to the clinic, nor have these genomic markers been used to inform clinical care.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is plausible that the immune and metabolic system dysfunction resulting from DAMP-induced activation of the TLR/mTOR/PPARγ pathway is responsible for poor patient outcomes. Although previous studies have explored immunological dysfunction during burn injury, no study has identified biomarkers, which can inform the clinical decision-making to assess patients’ immune status, contributing to poor patient outcomes [ 17 ]. Here, an unbiased survey of immune and metabolic gene expression was performed within peripheral blood monocytic cells (PBMCs) obtained early after injury (<48 h) from burn patients, with and without inhalation injury.…”
Section: Introductionmentioning
confidence: 99%
“…Much progress has been made in understanding the immunopathogenesis of burns and disorders of innate and adaptive immunity. Immunobiochemical markers predictive of sepsis, such as cytokines, growth factors, C-reactive protein, procalcitonin, presepsin, matrix metalloproteinases, reactive oxygen species, nitric oxide and hemostasis parameters, should be monitored to allow the timely initiation of a specific therapy [465]. However, traditional indicators of sepsis show poor performance, mainly due to hypermetabolic and inflammatory reactions after burns.…”
Section: Systemic Antibiotic Therapymentioning
confidence: 99%